Environmental policy and directed technological change: Evidence from the European carbon market - Raphael Calel; Antoine Dechezleprêtre (Fondazione Eni Enrico Mattei (FEEM), 2012)
The European Union Emissions Trading Scheme (EU ETS) has aimed to encourage the development of low-carbon technologies by putting a price on carbon emissions. Using a newly constructed data set that links 8.5 million European companies with their patenting history and their regulatory status under EU ETS, we investigate the hypothesis that the EU ETS has encouraged development of low-carbon technologies. Exploratory data analysis reveals a rapid increase in low-carbon patenting activities at the EPO since 2005, especially among EU ETS regulated companies during the Scheme's second phase. Naive estimates obtained by comparing EU ETS and non-EU ETS firms suggest that the Scheme may be responsible for up to 30% of the increase in low-carbon patenting of regulated companies. However, more refined estimates that combine matching methods with difference-in-differences provide evidence that the EU ETS has not impacted the direction of technological change. This finding appears to be robust to a number of stability and sensitivity checks. While we cannot completely rule out the possibility that the EU ETS has impacted only large companies for which suitable unregulated comparators cannot be found, our findings suggest that the EU ETS so far has had at best a very limited impact on low-carbon technological change.
Keywords: Q54; Q58; 330; Directed Technological Change; EU Emissions Trading Scheme; Policy Evaluation